Interaction of a three-level atom and a field with a time-varying frequency in the context of triangular well potentials: An exact treatment - Bahaaudin Raffah; K. Berrada; S. Abdel-khalek; E.M. Khalil; as Al-Hadeethi; Mohamed Ridza Wahiddin (ELSEVIER, 2024)
Chaos, Solitons & Fractals Volume 139, October 2020